What lessons Ethiopia could draw from China's township and village enterprises led rural industrialization? A thematic synthesis - Melkamu Tadesse Wazza; Sisay Belay Bedeke (Research in Globalization, 2022)
Despite managing rapid economic growth and demonstrating poverty reduction, Ethiopia did not achieve growth-enhancing rural transformation. A need to understand how to realize this can be obtained by synthesizing lessons from countries that have already attained it. In light of this, the purpose of the review was to carry out a thematic synthesis of China's rural industrialization through the Township and Village Enterprises (TVEs) and generate context-specific lessons that can inform Ethiopia's rural industrialization. Building on qualitative data management using the thematic synthesis approach, the review process involved extracting and coding data as well as developing, analyzing, and synthesizing themes from finally selected 46 peer-reviewed journal articles. The review and synthesis processes identified three major driving forces behind China's growth miracle. These were policy drivers, entrepreneurial drivers, and sociocultural drivers. The finding showed that the driving forces were successfully held together with effective institutions as a core driving force to form a rural industrialization framework (RIF). The major lesson that could be drawn is China's capability in building effective institutions. The RIF provides a holistic perspective in promoting the planning and implementation process of rural industrialization. Ethiopia can achieve successful rural industrialization and subsequent structural transformation by building and advancing effective formal and informal institutions with its own pragmatic, innovative, and sustainable means.
Keywords: 330; Driving Forces; Effective Institutions; Rural Industrialization Framework; Thematic Synthesis; Township and Village Enterprises (TVEs)